Economic Agglomeration and District-Level Carbon Emissions in Indonesia - Ryvanu Adi Nugroho; Djoni Hartono (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study contributes to the literature by incorporating employment density as a proxy of economic agglomeration into an extended STIRPAT framework to examine its nonlinear relationship with district-level carbon emissions in Indonesia. Research Objectives: This study aims to investigate whether economic agglomeration promotes emission efficiency or intensifies environmental pressure, and to identify potential nonlinear dynamics across Indonesian districts. Research Methods: This study employs a balanced panel dataset of 514 districts and municipalities in Indonesia over the period 2017–2024. A two-way fixed-effects model is estimated within an extended STIRPAT framework, with a quadratic specification to capture nonlinear effects. Empirical Results: The results indicate that economic agglomeration is associated with lower carbon emissions per capita, suggesting efficiency effects. However, the nonlinear estimation reveals a U-shaped relationship: agglomeration reduces emissions at lower levels but increases environmental pressure beyond a threshold. The findings also indicate substantial regional heterogeneity. Implications: The results suggest that agglomeration does not inherently lead to environmental improvements. Differentiated policies should strengthen regional growth and efficiency in low-density areas while prioritizing low-carbon transitions and congestion mitigation in dense regions. JEL Classification: Q56, R12, O18 How to Cite:Nugroho, R.A. & Hartono, D. (2026). Economic Agglomeration and District-Level Carbon Emissions in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 15(2), 471-486. https://doi.org/10.15408/sjie.v15i2.50229.